Adiposity and asthma in adults: a bidirectional Mendelian randomisation analysis of The HUNT Study. Issue 3 (14th October 2019) - Sun, Yi-Qian; Brumpton, Ben Michael; Langhammer, Arnulf; Chen, Yue; Kvaløy, Kirsti; Mai, Xiao-Mei
Abstract : Background: We aimed to investigate the potential causal associations of adiposity with asthma overall, asthma by atopic status or by levels of symptom control in a large adult population and stratified by sex. We also investigated the potential for reverse causation between asthma and risk of adiposity. Methods: We performed a bidirectional one-sample Mendelian randomisation (MR) study using the Norwegian Nord-Trøndelag Health Study population including 56 105 adults. 73 and 47 genetic variants were included as instrumental variables for body mass index (BMI) and waist-to-hip ratio (WHR), respectively. Asthma was defined as ever asthma, doctor-diagnosed asthma and doctor-diagnosed active asthma, and was further classified by atopic status or levels of symptom control. Causal OR was calculated with the Wald method. Results: The ORs per 1 SD (4.1 kg/m 2 ) increase in genetically determined BMI were ranged from 1.36 to 1.49 for the three asthma definitions and similar for women and men. The corresponding ORs for non-atopic asthma (range 1.42–1.72) appeared stronger than those for the atopic asthma (range 1.18–1.26), but they were similar for controlled versus partly controlled doctor-diagnosed active asthma (1.43 vs 1.44). There was no clear association between genetically predicted WHR and asthma risk or between genetically predicted asthma and the adiposity markers. Conclusions: Our MR study provided evidence of a causal association of BMI with asthma in adults, particularly with non-atopic asthma. There was no clear evidence of a causal link between WHR and asthma or of reverse causation.